The Importance of Cash and Bank Management and Inspection: An Education - Chelsya Chelsya (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: The main objective of this PKM is to educate students at Ricci I High School in Jakarta on the importance of effective, secure, and efficient cash and bank management. This activity is designed to give students a deep understanding of how to identify, record, classify, and report cash and bank transactions, including the cash and bank audit process. Research Design and Methodology: The PKM implementation method consists of three stages, namely planning, implementation, and dissemination of activity results. In the implementation stage, an educational approach is used through the delivery of materials, case-study-based training, and post-test learning evaluation. The training participants are high school students from Ricci 1 Jakarta, Indonesia, selected for their interest in accounting and financial management. Findings and Discussion: The results of the activity show that this PKM successfully increased students' knowledge of cash and banking concepts and basic auditing practices, including auditing techniques, transaction documentation, cash calculation reports, bank reconciliation, and balance confirmation. Based on the post-test results, participants' understanding reached 92%, indicating the effectiveness of the interactive learning method used. Implications: This activity can improve students' financial literacy and awareness of accountability. In practical terms, this PKM fosters positive synergy between universities and partner schools and serves as a model for practice-based learning that can be applied in secondary education to develop superior, integrity-driven human resources.